2007
DOI: 10.1177/183693910703200208
|View full text |Cite
|
Sign up to set email alerts
|

Preparing Children for School—Benefits and Privileges

Abstract: THE IMPORTANCE OF carefully planned transition programs for children commencing school has been advocated in the literature. These programs should be based on sound principles of transition and reflect the voices of parents, preschool and school staff, and children. A variety of practices exists, and children's participation in transition programs also varies. This paper reports a study about the participation of children and their parents in different transition activities, differences in this participation b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
10

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 12 publications
2
12
0
10
Order By: Relevance
“…To further explore the nature of Social-emotional school readiness with individual clients, we believe that the four subscales are good vehicles for further discussion. In the process of discussion and exploration, we agree with Blair and Raver (2015), Dockett and Perry (2005) and Margetts (2007) assumptions that successful transitions to school are based substantially on social skills and are facilitated by responsive relationships. Since the transition to school could be viewed as an individual's readiness to be involved in the process in children's lives (Denham, 2006), the impact of children's emotions and social relationships on later schooling and attainment, this is an important area to study and needs further examination.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…To further explore the nature of Social-emotional school readiness with individual clients, we believe that the four subscales are good vehicles for further discussion. In the process of discussion and exploration, we agree with Blair and Raver (2015), Dockett and Perry (2005) and Margetts (2007) assumptions that successful transitions to school are based substantially on social skills and are facilitated by responsive relationships. Since the transition to school could be viewed as an individual's readiness to be involved in the process in children's lives (Denham, 2006), the impact of children's emotions and social relationships on later schooling and attainment, this is an important area to study and needs further examination.…”
Section: Discussionsupporting
confidence: 71%
“…This scale, which was developed in South Africa, incorporates four subscales (self-regulation, self-awareness, social relationships and coping). This concept is a relative term that is socially and culturally constructed, and perceptions of it differ from community to community (Grace & Brandt, 2005;Margetts, 2002Margetts, ,2007. The only assessment instruments created in Iran, have been developed to measure the construct of school readiness, including home to school transition inventory (Sadeghi, Motamedi, & Vkilizadeh, 2016) which contains subscales(anxiety and incompatibility).…”
Section: Communication Skills and General Knowledgementioning
confidence: 99%
“…The level of parenting is believed to have a great impact on educational outcomes and is a determining factor in the child's future development and well-being. Furthermore, many studies have shown that there is a remarkable relationship between family's income and socio-economic situation, and the achievement of school literacy and thus the smooth transition of children to Primary school [37,[40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…Parents know their children well and can make a valuable contribution to a transition program. This could be done by inviting parents to participate in the program [42,46] to include their opinions on the design and operation of the program [47] and to share ideas and information about their children's transition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation